Pedagogi Fiqih Reflektif: Pengembangan Model Pembelajaran Fiqih Berbasis Mindful Learning untuk Internalisasi Nilai Ibadah - Dina Awaliyah; Rahma Dinda; Hana Kamilah; Abdul Fadhil (Advances In Education Journal, 2025)
The study of Fiqh often devolves into ritual formalism, focusing solely on procedural aspects (valid/invalid) and neglecting the substantive, affective values of worship. This leads to a spiritual disconnect, where students perform rituals without internalizing their impact. This conceptual study aims to address this issue by developing the Reflective Fiqh Pedagogy model, employing library research rooted in Fiqh philosophy (Maqashid), Islamic spiritual psychology (khusyuk), and modern mindfulness pedagogy. The data analysis resulted in the Reflective Fiqh Pedagogy model, which is built on three foundations (Fiqh Philosophy, Sufi Spirituality, and Mindfulness Psychology) and four syntaxes: (1) Conceptualization & Intention, (2) Full-Conscious Intervention, (3) Guided Reflection, and (4) Behavioral Connection. This model offers a theoretical solution to transform Fiqh learning from a cognitive-mechanistic approach to an affective-reflective one, thereby facilitating the genuine internalization of worship values.